Rice glycosyltransferase OsDUGT1 is involved in heat stress tolerance by glycosylating flavonoids and regulating flavonoid metabolism - Guang-rui Dong; Shu-man Zhao; Yi Ding; Yu-qing Ma; Xing-mei Ma; Chong-lin Liu; Bing-kai Hou (Frontiers in Plant Science)
One significant environmental element influencing the growth and yield of rice (Oryza sativa L.) is high temperature. Nevertheless, the mechanism by which rice responds to high temperature is not fully understood. A rice glycosyltransferase gene, OsDUGT1, was identified as a heat-responsive gene in this investigation. Its function was studied by overexpression and knockout methods. The results showed that under heat stress, OsDUGT1 overexpression lines (OsDUGT1-OE) increased the survival rate of rice, while Osdugt1 knockout lines (Osdugt1-ko) decreased the survival rate compared to wild type (ZH11). In addition to rice, heat stress tolerance was also improved by ectopic expression of OsDUGT1 in transgenic Arabidopsis thaliana plants. We observed that ROS scavenging ability, malondialdehyde accumulation, and the ion leakage are relevant to the expression level of OsDUGT1. Through enzyme activity analysis, we found that OsDUGT1 could glycosylate flavonoid compounds. Correspondingly, the loss of OsDUGT1 function caused a significant decrease in endogenous flavonoid accumulation in rice, which was demonstrated by our metabolomics analysis. Additionally, our transcriptomic analysis of Osdugt1 mutant lines under heat stress condition indicated that mutation of OsDUGT1 can reduce the transcriptional activity of heat response related genes, antioxidant enzyme genes and other genes involved in the flavonoid biosynthetic pathway. In summary, our work revealed that OsDUGT1 plays a crucial role in adjusting and balancing the overall plant metabolism and transcription under heat stress through glycosylation of flavonoids, and offers a key prospect gene for breeding efforts to enhance crop heat tolerance under the trend of climate warming all over the globe.